On the Siphonaptera collected by Dr. J.M. de la Barrera in the province of Mendoza during 1939 : (with 34 figures) - Jordan, Karl (1942)
Fil: Jordan, K. Departamento Nacional de Higiene. Instituto Bacteriológico; Argentina